Taiping bikes & beds / Shaiful Azli Muhamad Surol … [et al.] - Muhamad Surol, Shaiful Azli; Muhyi, Zamari; Abdul Hadi, Muhamad Zamzamir; Azmi, Ezwani (Division of Research and Industry Linkages, 2017)
Taiping Bikes & Beds inspired in the context o f the concept o f themed accommodations 'Beds & Breakfasts ’ which provides basic accommodation and hostel for guests and combining elements of the tour in free and easy and guided tours. A combination o f stay experience and various old bicycle rental at one price as the main attraction to tourists in the state for domestic tourists and abroad for international tourists specifically for single travelers, backpackers, flash packers, young travelers and young family travelers. This initiative highlighting the Act Tourism and Think Tourism towards the forty (40) heritage trail gazette by the tourism state o f Perak by offering various kinds o f trips based on the trail route by local council o f Taiping. The efforts as to educate local people and tourists as compilation of Heritage Tourism and Arts Tourism approach,